#TITLE_ALTERNATIVE# - BUDIARTO (NIM 28097017), ANTON
Incoming flow of passenger ships to Benoa - Bali Port increase continually year by year. Nevertheless, this condition was not accompanied with sufficient availability of port facilities, so the level of services provided for both passenger and cargo ships were low. It could be seen from the existence of mixed service between passenger and cargo ships in berth Multipurpose with length of 290 meters because not available for berth passenger ships specifically. The problem solving alternative to the conditions are to : 1. Develop new port. 2. Expand the existing port with additional berth length specifically for passenger ship. 3. Improve the efficiency of loading and unloading system. The first alternative could not be carried out in a short time basis due to some constraints (funds, time, etc.). On that account, analyses of the second and third alternatives were conducted with analytical queuing model using computer simulation. The estimation of number of passenger and cargo ships for year 1999 to 2010 using forecasting methods with linear regression or non linear regression was used as an input for analytical queuing model on computer simulation. As a result of queuing analysis with computer simulation, it is found that in the beginning of 1998 the applied existing scenario (mixed system/scenario 1) would no longer be matched with the condition due to the BOR and the WTR in the Multipurpose berth would be greater then UNCI AD requirements. Thus, from 1998 to 2001 the suitable scenario to be applied had to be the second scenario ( special service system in which BT average reduced to 20 %). As for between 2002 to 2010 the second and the third scenario could be applied suitably on the account of existing constraints ( special service system in which BT average reduced to 20 % and additional berth length specifically for passenger ship 200 meters).